Contractual relations between European VC-funds and investors: The impact of reputation and bargaining power on contractual design - Daniel Schmidt; Mark Wahrenburg (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The paper explores factors that influence the design of financing contracts between venture capital investors and European venture capital funds. 122 Private Placement Memoranda and 46 Partnership Agreements are investigated in respect to the use of covenant restrictions and compensation schemes. The analysis focuses on the impact of two key factors: the reputation of VC-funds and changes in the overall demand for venture capital services. We find that established funds are more severely restricted by contractual covenants. This contradicts the conventional wisdom which assumes that established market participants care more about their reputation, have less incentive to behave opportunistically and therefore need less covenant restrictions. We also find that managers of established funds are more often obliged to invest own capital alongside with investors money. We interpret this as evidence that established funds have actually less reason to care about their reputation as compared to young funds. One reason for this surprising result could be that managers of established VC funds are older and closer to retirement and therefore put less weight on the effects of their actions on future business opportunities. We also explore the effects of venture capital supply on contract design. Gompers and Lerner (1996) show that VC-funds in the US are able to reduce the number of restrictive covenants in years with high supply of venture capital and interpret this as a result of increased bargaining power by VC-funds. We do not find similar evidence for Europe. Instead, we find that VCfunds receive less base compensation and higher performance related compensation in years with strong capital inflows into the VC industry. This may be interpreted as a signal of overconfidence: Strong investor demand seems to coincide with overoptimistic expectations by fund managers which make them willing to accept higher powered incentive schemes.
urn:nbn:de:hebis:30-10207
Keywords: G32; 330; Venture Capital; Contracting; Limited Partnership; Funds; Principal Agent; Compensation; Covenants; Reputation; Bargaining Power; Risikokapital; Investmentfonds; Vertrag; Lieferanten-Kunden-Beziehung; Prestige; Schätzung; EU-Staaten